L’accueil au musée des publics en situation de handicap ou le long chemin vers un musée accessible - Reichhart, Frédéric (Muséologies, 2023)
The new definition of a museum put forward in 2022 by the International Council of Museums (ICOM) affirms the importance of a museum “open to the public, accessible and inclusive” and that “fosters diversity and sustainability”: the principles of accessibility, inclusion and participation are becoming a requirement as new norms for a museal institution and the evolution of its role and missions. They embody the necessary conditions to dust off the image of a cloistered museum, disconnected from its publics, and to build a welcoming museum space for active engagement with all publics. Still, beyond the affirmation of this political discourse, accessibility, whether seen by professionals as an injunction or a conviction, indeed an opportunity, is lagging; a study conducted in France in 2017 on accessibility to the culture for people with disabilities shows a number of difficulties in accessing culture, which throws the museal offer into question: how is the accessible offer structured for visitors with disabilities? And what is its participatory scope? To answer these questions, this article proposes to outline the content and evolution of this offer. Thus, firstly, the aim is to describe and present the sociopolitical and ideological context of museum accessibility in France; it looks back at the influence of cultural democratization as well as the emergence of inclusive pressure and accessibility, bolstered since 1975 by a legal framework. Secondly, the article will focus on the evolution of welcoming publics with disabilities and the variety of arrangements made to unite accessibility and participation.